THE EFFECT OF AUDIT TENURE, FIRM REPUTATION, AND AUDIT FEES ON AUDIT QUALITY WITH AUDIT COMMITTEE AS A MODERATING VARIABLE - Veri Dewi, Santi; Deni Iskandar (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
Abstract: Audit quality is a key factor in ensuring that a company's financial reports provide accu-rate and reliable information to external stakeholders. Good audit quality helps maintain integ-rity and transparency in financial reporting, thereby influencing business decision-making. However, in recent years, especially after a series of accounting scandals involving auditors, public trust in the ability of auditors to maintain audit quality has eroded. This research aims to explain and analyze the factors influencing audit quality, particu-larly in the context of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange during the period 2020-2022. Several key factors are the focus of this study. First, the research attempts to identify the influence of auditor tenure on audit quality. Audit tenure refers to the length of the relationship between the auditor and the audited company. Whether longer auditor tenure improves or harms audit quality is one of the questions to be answered. Second, the reputation of Public Accounting Firms (PAFs) is also considered to have a significant im-pact on audit quality. The reputation of PAFs reflects how well they perform audit tasks and instills confidence in stakeholders about audit results. Third, the amount of audit fees is also a relevant factor in this study. The size of audit fees can affect auditor independence and overall audit quality. This research also considers the role of the audit committee as a moderating vari-able in the influence of auditor tenure, PAF reputation, and audit fees on audit quality. The au-dit committee is considered an internal oversight entity that can influence how audits are con-ducted and ensure their integrity. The research method used is quantitative with a moderating technique. Secondary data from financial reports of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange during the period 2020-2022 are used as the data source. The research sample is se-lected through purposive sampling, and data analysis is performed using SPSS software version 27. The results of this research indicate that audit tenure, PAF reputation, and audit fees do not affect audit quality. Additionally, the audit committee does not moderate the influence of audit tenure, PAF reputation, and audit fees on audit quality. The findings of this research are expected to provide deeper insights into the factors in-fluencing audit quality and the important role of the audit committee in this context. These re-sults can also serve as a guide for companies and regulatory authorities in enhancing integrity and transparency in financial reporting. In conclusion, audit quality has significant implica-tions in the business world, and this research aims to provide a better understanding of it. Keywords: audit tenure, Public Accounting Firm reputation, audit fee, audit quality, audit committee